Beneficial effects of sunitinib on tumor microenvironment and immunotherapy targeting death receptor5. (1st February 2019) - Tsukita, Yoko; Okazaki, Tatsuma; Ebihara, Satoru; Komatsu, Riyo; Nihei, Mayumi; Kobayashi, Makoto; Hirano, Taizou; Sugiura, Hisatoshi; Tamada, Tsutomu; Tanaka, Nobuyuki; Sato, Yasufumi; Yagita, Hideo; et al.
ABSTRACT: Tumor-associated blood vessels and lymphatics are abnormal and dysfunctional. These are hallmarks of the tumor microenvironment, which has an immunosuppressive nature, such as through hypoxia. Treatment with anti-death receptor5 (DR5) monoclonal antibody MD5-1, which induces tumor cell death, is a potent anti-tumor immunotherapy. Generally, MD5-1 induces cell death mainly via antigen presenting cells (APCs) and generates tumor-specific effector T cells. To date, the effects of a simultaneous functional improvement of abnormal blood vessels and lymphatics on the immune microenvironment are largely unknown. A combination therapy using sunitinib, vascular endothelial growth factor (VEGF) and platelet-derived growth factor receptor inhibitor, and MD5-1 substantially inhibited tumor growth. Sunitinib improved pericyte coverage on endothelial cells and the expression levels of regulator of G-protein signaling 5, suggesting blood vessel normalization. Sunitinib also increased lymph flow from tumors to central lymph nodes, suggesting improved lymphatic function. In concordance with improved vasculature functions, sunitinib alleviated the tumor hypoxia, suggesting an improved tumor microenvironment. Indeed, the combination therapy induced strong activation of CD8 + T cells and dendritic cells in draining lymph nodes. The combination therapy reduced the ratio of immune-suppressive T regulatory cells in the tumors and draining lymph nodes. The combination therapy enhanced the numbers and activation of tumor-infiltrating CD8 + T cells. CD4 and/or CD8 depletion, or APC inhibiting experiments showed the contribution of CD8 + T cells and APCs to the combination therapy. These findings suggest that targeting blood vessels and lymphatics may have potential benefits for immunotherapy mediated by CD8 + T cells and APCs.